The mechanism of suppression of quantum transitions (quantum whirligig) - Buts, V.A. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
The mechanism allowing to stabilize of a state of quantum systems is considered. And, the initial condition can correspond both for excited state and for not excited, stationary state. The considered mechanism for the first time was offered for the excited states, and has received the name as quantum whirligig (QWE). In this work the close connection of the considered mechanism with Zeno effect is shown. The considerations are stated, that many experimental results, which are interpreted as observation of Zeno effect, apparently, correspond to QWE. Рассматривается механизм, позволяющий стабилизировать состояния квантовых систем, причем начальные состояния могут соответствовать как возбужденному, так и невозбужденному стационарным состоянием. Рассматриваемый механизм впервые был предложен для возбужденных состояний и получил название квантовая юла. В работе показана тесная связь рассматриваемого механизма с эффектом Зенона. Высказаны соображения, что многие экспериментальные результаты, которые интерпретируются как наблюдение эффекта Зенона, повидимому, соответствуют эффекту квантовой юлы. Розглядається механізм, який дозволяє стабілізувати стан квантових систем. Причому, початковий стан може відповідати як збудженому, так і незбудженому стаціонарному стану. Механізм, який розглядався вперше, був запропонований для збуджених станів і одержав назву квантової юли. В роботі показано тісний зв'язок механізму, який розглядається, з ефектом Зенона. Виказані розуміння, що багато-які експериментальні результати, які інтерпретуються як спостереження ефекту Зенона, можливо, відповідають ефекту квантової юли.